2005
DOI: 10.1177/153331750502000313
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of everyday behavior in Alzheimer's disease patients: Its significance for diagnostics and prediction of disease progression

Abstract: In addition to cognitive decline, current diagnostic criteria for Alzheimer's disease (AD) require evidence of impaired social and/or occupational functioning. The Nurses' Observation Scale for Geriatric Patients (NOSGER) is used to rate the frequency of disturbances in everyday behaviors and, although not specifically developed for this purpose, is often applied for diagnostic purposes. The NOSGER assesses six dimensions: Memory, Instrumental Activities of Daily Living (IADLs), Self-Care (ADL), Mood, Social B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…52,53,58 In dementia, psychosis, hyperactivity, agitation and physical aggression were associated with greater cognitive impairment. 35,38,6365,70 Symptoms may be most common in moderate dementia, followed by a declining or stable course in the final stages of dementia. 35,63,64 However, heterogeneity in the pattern of findings across studies investigating the associations between BPSD and cognitive function prevented us from drawing more specific conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52,53,58 In dementia, psychosis, hyperactivity, agitation and physical aggression were associated with greater cognitive impairment. 35,38,6365,70 Symptoms may be most common in moderate dementia, followed by a declining or stable course in the final stages of dementia. 35,63,64 However, heterogeneity in the pattern of findings across studies investigating the associations between BPSD and cognitive function prevented us from drawing more specific conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with dementia, psychosis, hyperactivity, agitation and physical aggression were associated with greater cognitive impairment. 26,35,38,[63][64][65] In contrast, Marin et al found no association in dementia between cognitive impairment and depression, delusion, agitation and irritability. 66 Four studies found that symptoms increased with cognitive decline in the early stages of dementia and were most commonly seen in moderate dementia, followed by a declining or stable course in the final stages of dementia.…”
Section: Cognitive Function and Bpsd Developmentmentioning
confidence: 96%
“…In einer Studie von Brunner und Spiegel [5] ergaben sich Hinweise, dass einzelne Dimensionen des NOSGER den Grad der kognitiven Beeinträchtigungen der untersuchten Patienten erfassten. Ebenso wurde in einer aktuellen Arbeit von Blasi et al [2] der NOSGER zusammen mit dem MMS als Screeninginstrument für Alzheimer-Demenz empfohlen, weil er in allen Dimensionen gut zwischen AlzheimerPatienten und Kontrollen differenzierte. Weil sich die Items der Verhaltenserfassung bei Patienten mit leichter Alzheimer-Demenz linear verschlechterten, betrachteten die Autoren ihn außerdem als geeignetes Instrument, zunehmende Verhaltensstörungen als Zeichen der Krankheitsprogredienz zu dokumentieren.…”
Section: Diskussionunclassified
“…Im Gegensatz zum CERAD wurde der NOS-GER (Nurses Observation Scale for Geriatric Patients) ursprünglich entwickelt, um als Pflegeinstrument die Alltagskompetenz von an Demenz erkrankten Patienten während pharmakotherapeutischer Interventionen zu erfassen [24]. Außer-dem scheint dieser Test aber auch geeignet zu sein, Alzheimer-Patienten von Kontrollen zu differenzieren, so dass ihm in Diagnostik und Verlaufsdokumentation der Alzheimer-Demenz eine gewichtigere Rolle zukommen könnte [2].…”
unclassified